Pseudopalavras favorecedoras para terapia fonológica - Bonini, Joviane Bagolin (2016)
The phonological disorder is a speech disorder that affects many children during the acquisition process. Phonological therapy aims to adapt the phonological system changed. There are several models and strategies that can be used in speech therapy. The aim of this study was to analyze favoring environments PB phonemes and from these create and validate a nonsense words list and check the therapeutic progress of children undergoing a new therapeutic approach using real words and and nonsense words. The study was developed in three stages: the analysis of the linguistic environment of the Portuguese phonemes, the creation and validation of nonsense words and the realization of phonological therapy. The sample of the first stage consisted of 58 with phonological disorders and aged between 4:00 and 8:00 years. The sample was composed of the 21446 words transcribed in Phonological Assessment of Children. The words were collected and analyzed in relation to the linguistic variable number of syllables, tonicity, position in word and syllable preceding context and the following context. Data were analyzed by statistical program Varbwin for each phoneme of the Portuguese. From the results calculated if the weight of each variant and measuring by quartiles set the values of the ranges favoring each phoneme. From the results obtained in this step we calculated the words sense of favoritism value and a nonsense words list was created. In the second stage of the research, the nonsense words list was evaluated by two groups of judges, both composed of 5 members. The first group performed a selection of the best nonsense words, and the second group ranked into categories. The results obtained with the judgment of the second group of judges were analyzed through the Content Validity Ratio. With this, a list of validated nonsense words was obtained. In the third stage of the research was applied a new therapeutic approach in 3 subjects with phonological disorder. In this approach some subjects were treated with the nonsense words and real words, and others only with real words. The target words used in therapy were obtained and had their favor value calculated from the data obtained in the first and second stage of this research. The results of the study allowed us to verify that each phoneme has personal linguistic environments. The nonsense words are resource that can be used in therapy. It concluded the new therapeutic approach with nonsense words and favoring environments is adequate for the treatment of phonological disorders.